Reply to Comment on COVID‐19 Deaths in Long Term Care Facilities ‐ A Critical Piece of the Puzzle. Issue 12 (2nd October 2020) - Lau‐Ng, Rossana; Caruso, Lisa B.; Perls, Thomas T.
Abstract : This letter comments on the letter by Tak-kwan Kong . Abstract : This letter comments on the letter by Tak-kwan Kong .